A Peptide-Based PD1 Antagonist Enhances T-Cell Priming and Efficacy of a Prophylactic Malaria Vaccine and Promotes Survival in a Lethal Malaria Model - Phares, Timothy W.; Kotraiah, Vinayaka; Karunarathne, Deshapriya S.; Huang, Jing; Browne, Cecille D.; Buontempo, Peter; Mansour, Marc; Noe, Amy R.; Wykes, Michelle N.; Pannucci, James; Tsuji, Moriya; Gutierrez, Gabriel M. (Frontiers in Immunology, 2020)
The blockade of programmed cell death-1 (PD1) and its ligand PDL1 has been proven to be a successful immunotherapy against several cancers. Similar to cancer, PD1 contributes to the establishment of several chronic infectious diseases, including malaria. While monoclonal antibodies (mAbs) targeting checkpoint receptors are revolutionary in cancer treatment, the immune-related adverse events (irAEs) may prevent their utilization in prophylactic and therapeutic treatments of infectious diseases. The irAEs are, in part, due to the prolonged half-life of mAbs resulting in prolonged activation of the immune system. As an alternative modality to mAbs, peptides represent a viable option because they possess a shorter pharmacokinetic half-life and offer more formulation and delivery options. Here, we report on a 22-amino acid immunomodulatory peptide, LD01, derived from a Bacillus bacteria. When combined prophylactically with an adenovirus-based or irradiated sporozoite-based malaria vaccine, LD01 significantly enhanced antigen-specific CD8+ T cell expansion. Therapeutically, LD01 treatment of mice infected with a lethal malaria strain resulted in survival that was associated with lower numbers of FOXP3+Tbet+CD4+ regulatory T cells. Taken together, our results demonstrate that LD01 is a potent immunomodulator that acts upon the adaptive immune system to stimulate T cell responses both prophylactically and therapeutically.